PENERAPAN MODEL ARCS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMP LABSCHOOL UNIVERSITAS TADULAKO PADA MATERI SUDUT-SUDUT SEGITIGA - Irsaf, Zulfira (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain a description about applying of Attention, Relevance, Confidence, Satisfaction (ARCS)Â  model can improve studentsâ learning outcomes in angles of a triangle material. The type of research is classroom action research. The design of this study referred to the model proposed by Kemmis and Mc. Teggart. This study was conducted in two cycles. The results of the study showed that through the application of ARCS model can improve student learning outcomes, by following the steps, namely Â (1) creating and focusing studentâs attention by praying, checking attendance and inform the material to be learned to the students, (2) giving apperception to the students form of matter that is shown with the help of broadcast material, (3) delivering the learning objectives and benefits of learning by showing pictures of everyday life that relate to the material, (4) delivering the learning materials, in the form of directives in the task delivery in student worksheet (SWS), (5) providing tutoring session to students who need guidance, (6) gaining studentsâ performance by providing the opportunity for some groups to present their work to the class, (7) providing feedback in the form of positive comments and compliments on the work of students, (8) evaluating studentsâ learning outcomes by providing practice questions to students, (9) and strengthening the retention and transfer by giving homework and gives a message that can motivate students